THE IMPACT OF THE SURGICAL LIAISON NURSE ON PATIENT SATISFACTION IN THE PERIOPERATIVE SETTING - Stephens-Woods, Kim (Operating Room Nurses Association of Canada Journal, 2008)
Improving patient satisfaction, communication, and the reduction of anxiety, is an important factor in perioperative care. The introduction of a surgical liaison nurse (SLN) will have significant impact. Through the SLN’s ability to focus on the patient and to transition with the patient through all areas of the surgical experience, the resulting care will be less fragmented and the improvement will be evident.